Study of Anisotropic LRS Bianchi type-I Universe with Variable Deceleration Parameter in f (R, T) Gravity (International Journal of Scientific Research in Science and Technology, 2024)
In the present investigation LRS Bianchi type-I universe with variable deceleration parameter in f (R, T) theory of gravity is considered. I obtain the gravitational field equations in the metric formalism, which follows from the covariant divergence of the stress-energy tensor. The field equations correspond for a specific choice of f (R, T) = f1 (R)+ f2 (T), with the individual superior functions and . Allowing for time dependent deceleration parameter the solutions of the field equations and some physical and geometric properties of the model along with physical acceptability of the solutions have also been discussed in details.